Balancing scores for simultaneous comparisons of multiple treatments - Yatracos, Yannis G. (My University, 2015)
Criteria based on the T-treatment's posterior density, qT(t|x), provide conclusively a balancing-sufficient score, s, and the coarsest, c, for the treatments indexing the X-covariates' unknown density. Strong ignorability of treatment assignment given s, allows using s and c for simultaneous comparisons of multiple treatments.
Keywords: Balancing factorization criterion; Causal inference; Matching; Propensity function; Sufficient statistic